Problems аnd Prospects оf Development аnd Rational Use оf the Local Budget оf а Rural Territory - S. G. Chepik; O. V. Chepik (Финансы: теория и практика)
The purpose of the article is to study the issues of development and rational use of local budgets of agro-industrial territories. The authors have analyzed specific indicators of the local budget typical for the Ryazan region for 2014– 2016 — the Kaninsky rural settlement of the Sapozhkovsky District. Due to the economic-statistical and SWOT-analysis, some problem aspects have been revealed. In particular, local authorities do not have an opportunity to independently draw up their own full budgets. As a rule, they are pumped up at the expense of financial sources not controlled by the rural administrations. This has a number of negative consequences: it does not contribute to revitalizing and rationalizing actions of the local authorities to replenish the tax potential of the territory; it reduces the administration’s responsibility for the budget execution and meeting commitments to the public; it causes dependency of local rural administrations while developing the revenue part of the budget; it does not contribute to the development of economic initiatives. The authors conclude that to improve the development and rational use of local budgets of rural settlements, it makes sense: to consolidate the results-oriented principles of medium-term planning and budgeting; to accept the requirement for further decentralization of the budget system and to provide real budget independence; to provide effective control over budgets of all levels and their real transparency.